What is the appropriate dose for spironolactone as a fourth‐line agent in treating resistant hypertension?. Issue 6 (June 2017) - Moonesinghe, Kushan; Talati, Khyati
Abstract : Bottom line : In patients with resistant hypertension, 48% to 73% can be controlled by adding 25 to 50 mg spironolactone. Increasing to 100 mg may not have any more effect (SOR: C, RCT and cohort study with disease‐oriented outcomes).